2012
DOI: 10.15580/gjms.2012.5.110712237
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal pregnancy body mass index as a measure of pregnancy weight gain on neonatal birth weight in Maiduguri metropolitan council of Borno state, Nigeria

Abstract: Aim:The effect of maternal pregnancy body mass index as a measure of pregnancy weight gain on neonatal birth weight outcome in the labor ward of the University of Maiduguri Teaching Hospital. Methods: One hundred and four mother-neonatal pairs were selected using systematic random sampling method. Maternal pregnancy body mass index was calculated from maternal weight and height using the formula maternal body weight divided by the square of maternal height in kilogram/meter square (kg/m 2 ), and neonatal birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The pre-pregnancy BMI of the participants was close to what was reported in Nigeria [10] but was lower than what was reported in another study in Nigeria and also in Brazil [20, 21]. Our low BMI could be explained by the fact that our study enrolled only women who were pregnant for the first or second time and the majority were relatively young, mean age of 20.9 years.…”
Section: Discussionsupporting
confidence: 75%
“…The pre-pregnancy BMI of the participants was close to what was reported in Nigeria [10] but was lower than what was reported in another study in Nigeria and also in Brazil [20, 21]. Our low BMI could be explained by the fact that our study enrolled only women who were pregnant for the first or second time and the majority were relatively young, mean age of 20.9 years.…”
Section: Discussionsupporting
confidence: 75%
“…6 While study done by Maduguari et al showed that there is no relation between maternal weight gain and newborn weight. 7 Total number of patients in the age group 26-30 years is 33 and out of these 33, 7 patients gained weight <11kg. Out of these 7 patients 2 patients delivered newborn <2.5kg and 5 deliver with our study.…”
Section: Discussionmentioning
confidence: 99%